2020
DOI: 10.7150/ijbs.49890
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation in Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is a blinding eye disease which incidence gradually increases with age. Inflammation participates in AMD pathogenesis, including choroidal neovascularization and geographic atrophy. It is also a kind of self-protective regulation from injury for the eyes. In this review, we described inflammation in AMD pathogenesis, summarized the roles played by inflammation-related cytokines, including pro-inflammatory and anti-inflammatory cytokines, as well as leukocytes (macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(122 citation statements)
references
References 163 publications
(190 reference statements)
1
103
0
2
Order By: Relevance
“…These angiography imaging techniques might provide additional information about RPE changes 18 , 35 . Fourth, the detection of intraretinal RPE changes in the present study, based on the presence of melanin and lipofuscin, was limited by the possible presence of infiltrating inflammatory cells 36 . If inflammatory cells ingested melanosomes and lipofuscin from disintegrating RPE cells, our imaging system might have misidentified those inflammatory cells as RPE cells.…”
Section: Discussionmentioning
confidence: 77%
“…These angiography imaging techniques might provide additional information about RPE changes 18 , 35 . Fourth, the detection of intraretinal RPE changes in the present study, based on the presence of melanin and lipofuscin, was limited by the possible presence of infiltrating inflammatory cells 36 . If inflammatory cells ingested melanosomes and lipofuscin from disintegrating RPE cells, our imaging system might have misidentified those inflammatory cells as RPE cells.…”
Section: Discussionmentioning
confidence: 77%
“…In wet AMD, the injured RPE cells have been found with augmented expression of IL-8 in addition to VEGF and monocyte chemoattractant protein-1 which attract monocytes from the choriocapillaris resulting in the breakdown of the blood–retina barrier and angiogenesis [ 107 ]. The activation of STAT3 by IL-6 receptor, a key mediator in subretinal fibrosis, promotes CNV and the levels of IL-6 is correlated with the size and activity of CNV in AMD patients [ 108 , 109 ]. Studies showed that dysbiosis of gut leads to increased intestinal permeability and a chronic low-grade inflammation characteristic of inflammaging, with elevated levels of IL-6, IL-1β, TNF-α, and VEGF-A leading to exacerbation of pathological angiogenesis [ 108 , 110 , 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of STAT3 by IL-6 receptor, a key mediator in subretinal fibrosis, promotes CNV and the levels of IL-6 is correlated with the size and activity of CNV in AMD patients [ 108 , 109 ]. Studies showed that dysbiosis of gut leads to increased intestinal permeability and a chronic low-grade inflammation characteristic of inflammaging, with elevated levels of IL-6, IL-1β, TNF-α, and VEGF-A leading to exacerbation of pathological angiogenesis [ 108 , 110 , 111 ]. Moreover, oxidative stress may also up-regulate VEGF expression in the retina and induce CNV.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related macular degeneration (AMD) is a chronic structural change in the macular area under multifactorial interaction of metabolism, functions, genetics, and the environment [ 140 ]. The most common cause of vision loss is the development of choroidal neovascularization, which is a common type of AMD [ 141 ].…”
Section: Non-oncologic Applications Of Photodynamic Therapymentioning
confidence: 99%